JNK Activation Turns on LPS- and Gram-Negative Bacteria-Induced NADPH Oxidase-Dependent Suicidal NETosis - Meraj A. Khan (Nature Portfolio, 2017)
Abstract Neutrophils cast neutrophil extracellular traps (NETs) to ensnare microbial pathogens. Nevertheless, the molecular rheostats that regulate NETosis in response to bacteria are not clearly established. We hypothesized that stress-activated protein kinase or c-Jun N-terminal Kinase (SAPK/JNK) is a molecular switch that turns on NETosis in response to increasing concentrations of lipopolysaccharide (LPS)- and Gram-negative bacteria. Here we show that Escherichia coli LPS (0111:B4; 10–25 μg/ml), but not phorbol myristate acetate (PMA), activates JNK in human neutrophils in a dose-dependent manner. JNK inhibitors SP600125 and TCSJNK6o, and a TLR4 inhibitor TAK242 suppress reactive oxygen species production and NETosis in LPS-, but not PMA-treated neutrophils. Diphenyleneiodonium suppresses LPS-induced NETosis, confirming that endotoxin induces NADPH oxidase-dependent NETosis. Immunoblots, Sytox Green assays, and confocal microscopy of cleaved caspase-3 and nuclear morphology show that JNK inhibition does not induce apoptosis in LPS-stimulated neutrophils. JNK inhibition also suppresses NETosis induced by two typical Gram-negative bacteria, E. coli and Pseudomonas aeruginosa. Therefore, we propose that neutrophils use a TLR4-dependent, JNK-mediated molecular sensing mechanism to initiate NADPH oxidase-dependent suicidal NETosis in response to increasing concentrations of LPS, and Gram-negative bacteria. The LPS-TLR4-JNK activation axis determines the fate of these cells: to be or not to be NETotic neutrophils.